Developing video education materials for the return of genomic test results to parents and adolescents - John A. Lynch; Michaela J. Idleburg; Melinda Butsch Kovacic; Kristin E. Childers-Buschle; Kevin R. Dufendach; Ellen A. Lipstein; Michelle L. McGowan; Melanie F. Myers; Cynthia A. Prows (Elsevier, 2022)
Objective: To describe the development, implementation, and revision of a video to provide information about genomic testing and the return of genomic research results to adolescents and parents. Methods: Formative, community-engaged research was conducted in three stages: development, implementation, and revision. Existing research participant advisory groups were used for focus groups and convenience sampling was used for interviews. Participants included parents, young adults without children, and adolescents. Transcripts of recorded sessions were used for formative analysis. Results: Video was the preferred format for delivering genomic testing information to adolescents during the development stage. During implementation, adolescents identified video length as an impediment to recall. During the revision stage, participants preferred the video in separate short segments, supported plan to require only one short video and leaving other short videos optional. Participants were divided on whether the required short video provided enough information, but all participants reported that watching additional videos would not have changed their decisions about receiving test results. Conclusion: Genomic education videos should be brief (<4 mins) to improve the odds that participants will view the entirety of any required video. Innovation: The development of participant materials should incorporate plans for monitoring implementation and plans for revising materials.